Cyanobacteria Desertifilum tharense NIOF17/006 as a novel aquafeed additive: effect on the growth, immunity, digestive function, and gene expression of whiteleg shrimp postlarvae - Ashour, Mohamed; Al-Souti, Ahmed Said; Mamoon, Ahmed; Ali, Fawzia S.; Elshobary, Mostafa E.; Mabrouk, Mohamed M.; Mansour, Ahmed I. A.; Mansour, Abdallah Tageldein; El-Haroun, Ehab; Abdelhamid, Ahmed F. (Frontiers in Marine Science, 2025)
This work investigated the molecular identification and potential application of the cyanobacterial strain Desertifilum tharense NIOF17/006 as a novel aquafeed additive for whiteleg shrimp (Litopenaeus vannamei) postlarvae (PLs). Morphological and molecular characterization confirmed the isolate as D. tharense, with the 16S rRNA sequence analysis showing high similarity (98.01%–98.53%) to the known strains of D. tharense. Biochemical analysis revealed that the isolate contains 37.74% protein, 5.52% lipid, and 21.25% carbohydrate, on a dry weight basis. An 8-week feeding trial for L. vannamei PLs evaluated the effects of dietary supplementation with D. tharense NIOF17/006 at doses of 0, 1, 2.5, and 5 g/kg diet. Compared with shrimp in the control group, shrimp fed D. tharense-supplemented diets had significantly higher feed utilization, growth performance, survival rate, and whole body composition. The nonspecific immunity parameters (i.e., lysozyme, superoxide dismutase, and catalase), as well as the digestive enzyme activity of amylase and lipase, were significantly enhanced in shrimp fed diets supplemented with cyanobacteria, while the malondialdehyde (MDA) levels decreased. The gene expression analysis revealed the upregulation of growth-related genes (growth hormone, insulin-like growth factor I, and insulin-like growth factor II) and the immune-related genes prophenoloxidase (proPO), superoxide dismutase (SOD), and lysozyme (Lys) in shrimp muscles with increasing cyanobacteria supplementation, particularly at doses of 2.5–5 g/kg diet. Moreover, the polynomial regression machine learning model predicts that the ideal supplementation level of the probiotic cyanobacteria D. tharense NIOF17/006 ranges from 3.4 to 4.2 g/kg diet. This study demonstrates the potential of D. tharense NIOF17/006 as a promising aquafeed additive for improvement of the growth, immunity, and overall health of L. vannamei PLs, opening a new avenue for sustainable aquaculture practices.